(untitled) (Al-Mukhtar Journal of Basic Sciences, 2026)
The emergence of antibiotic-resistant bacteria in drinking water sources poses a significant public health threat. This study examines the presence of antibiotic-resistant bacteria in four springs in Massa, Libya, and explores the impact of seasonal changes on antibiotic sensitivity. Water samples were collected from each spring during the autumn and winter of 2023, and antibiotic susceptibility tests were performed using different classes of antibiotics. The results revealed the presence of antibiotic-resistant strains of Escherichia coli, with significant interactions between seasonal changes, bacterial species, and antibiotic types. The study highlights the complex interplay between these factors, underscoring the need for a multifaceted approach to address antibiotic resistance in drinking water sources. The findings contribute to a deeper understanding of the dynamics influencing antibiotic resistance and provide valuable insights for the development of targeted strategies to mitigate this public health challenge.